Memorials, South West corner - Ghosh, Ayan (2023)
The interiors have hundreds of memorial plaques erected by friends and family members in memory of their loved ones. Memorials were also erected by the East India Company in honor of EIC officers and administrators who died of natural causes, perished at sea, or got killed in the line of duty in various military campaigns in the Bombay Presidency.